Phylogenetic relationships in Bulbostylis (Abildgaardieae: Cyperaceae) inferred from nuclear and plastid DNA sequence data. Issue 5 (4th July 2018) - Reutemann, Andrea G.; Ardissone, Rodrigo E.; López, María Gabriela; Muchut, Sebastián Elias; Boldrini, Ilsi; Vegetti, Abelardo Carlos; Giussani, Liliana Mónica
Abstract : Previous molecular phylogenetic analyses of the family Cyperaceae based on rbc L sequences showed Bulbostylis as paraphyletic, with B. atrosanguinea and B. hispidula forming a clade with Nemum spadiceum . On the contrary, phylogenetic analyses of the tribe Abildgaardieae based on nuclear (ITS ribosomal region) and plastid sequences ( trn L-F region) showed Bulbostylis as monophyletic, although they only incorporated four species of Bulbostylis and none of Nemum . In this work, we presented a phylogenetic hypothesis of Bulbostylis based on a comprehensive sampling, including species from different continents for the first time. New sequences of Abildgaardia, Crosslandia, Fimbristylis, and Nemum were included to test the monophyly of Bulbostylis . In total, 84 sequences of both ITS and trn L regions were generated. Analyses were performed using Bayesian inference, maximum likelihood, and parsimony. Ancestral state reconstruction was performed using ML, MCMC, and parsimony methods. In all analyses, Bulbostylis resulted paraphyletic as Nemum atracuminatum is nested within it. Most American species of Bulbostylis grouped together, but relationships amongst them appeared poorly resolved. Ancestral state reconstructions of native distribution suggest an African ancestor of Bulbostylis, with at least three introduction independent events of the species in America. Morphological diagnostic characters such as the 'style base permanence or detachment from the ripe achene', and the 'micromorphological patterns of the achene surface' are homoplastic in this phylogenetic context, and therefore unsuitable to propose infrageneric groupings within the Bulbostylis .